Improving green IT assessment tool using case-based reasoning technique - Chua, Xiao Ying (2019)
In this era of modernization, where technologies are the trend, it is important to take not of our surrounding too. As the saying goes, every action has a reaction. Despite the fact that technologies can bring us many benefits, but if is not well utilize, it can cause harms to the environment. Example such as efforts or move to help to reduce environment issues and to works towards UN sustainability goals. In order to know or measure their level of green practices, green assessment tool is there to act as a guide or as some might called it as a bench marker. Although, there are existing green assessment tools but there is inadequate existing green assessment tool with a recommendation feature. Recommendation feature is meant to aid users especially new user with their green practices. In this thesis, case-based reasoning will be the method used to produce this recommendation features. Besides that, this thesis will be applying Rapid Application Development Model. The expected result of this thesis is to improve an existing green assessment tool to provide recommendation to user. With this thesis research project, it can help to raise user’s level of green awareness and improve their practices.